Petrology and geochemistry of calc-alkaline volcanic and subvolcanic rocks, Dalli porphyry copper–gold deposit, Markazi Province, Iran - Ayati, F.; Yavuz, F.; Asadi, H.H.; Richards, J.P.; Jourdan, Fred (Taylor & Francis Inc., 2013)
Early Miocene igneous rocks associated with the Dalli porphyry ore body are exposed within the Urumieh-Dokhtar Magmatic Arc (UDMA). The Dalli porphyry Cu–Au deposit is hosted by subduction-related subvolcanic plutons with chemical composition from diorite to granodiorite, which intruded andesitic and dacitic volcanic rocks and a variety of sedimentary sequences. 40Ar/39Ar age data indicate a minimum emplacement age of ~21 million years for a potasically altered porphyritic diorite that hosts the porphyry system. The deposit has a proven reserve of 8 million tonnes of rock containing 0.75 g/t Au and 0.5% Cu. Chondrite-normalized rare earth element (REE) patterns for the subvolcanic rocks are characterized by light REE enrichments [(La/Sm) n  = 2.57–6.40] and flat to gently upward-sloping profiles from middle to heavy REEs [(Dy/Yb) n  = 0.99–2.78; (Gd/Yb) n  = 1.37–3.54], with no significant Eu anomalies. These characteristics are generated by the fractionation of amphibole and the suppression of plagioclase crystallization from hydrous calc-alkaline magmas. In normalized multi-element diagrams, all analysed rocks are characterized by enrichments in large ion lithophile elements and depletions in high field strength elements, and display typical features of subduction-related calc-alkaline magmas. We used igneous mineral compositions to constrain the conditions of crystallization and emplacement.Biotite compositions plot above the nickel–nickel oxide (NNO) buffer and close to oxygen fugacity values defined by the hematite–magnetite (HM) buffer, indicating oxidizing conditions during crystallization. Assuming a minimum crystallization temperature of 775°C, the oxygen (fO2) and water (fH2O) fugacities are estimated to be 10−10.3 bars (~ΔNNO+4) and ≤748 bars, respectively, during the crystallization of biotite phenocrysts. The temperature and pressure conditions, estimated from temperature–corrected Al-in-hornblende barometry and amphibole-plagioclase thermometry, suggest that the hornblende phenocrysts in Dalli rocks crystallized at around 780 ± 20°C and 3.8 ± 0.4 kbar. An alternative method using the calcic amphibole thermobarometer indicates that the Dalli magmas were, on average, characterized by an H2O content of 4.3 wt.%, a relatively high oxygen fugacity of 10−11.0 bars (ΔNNO+1.3), and a hornblende phenocryst crystallization temperature of 880 ± 68°C and pressure of 2.6 ± 1.7 kbar.